2020
DOI: 10.1186/s12883-020-01738-9
|View full text |Cite
|
Sign up to set email alerts
|

Vertical pons hyperintensity and hot cross bun sign in cerebellar-type multiple system atrophy and spinocerebellar ataxia type 3

Abstract: Background: The "hot cross bun" (HCB) sign, a cruciform hyperintensity in the pons on magnetic resonance imaging (MRI), has gradually been identified as a typical finding in multiple system atrophy, cerebellar-type (MSA-C). Few reports have evaluated the sensitivity of an HCB, including a cruciform hyperintensity and vertical line in the pons, which precedes a cruciform hyperintensity, in the early stages of MSA-C. Moreover, the difference in frequency and timing of appearance of an HCB between MSA-C and spino… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Although they did not refer to DWI characteristics in diagnosis, it still could be a potential source of bias. Fourthly, other image parameters including the vertical pons hyperintensity which has been reported to be more sensitive than “hot cross bun” sign and “swallow-tail” sign were not evaluated ( 16 , 20 ). Finally, the absence of a definite postmortem diagnosis increases the likelihood of misdiagnosis in our patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they did not refer to DWI characteristics in diagnosis, it still could be a potential source of bias. Fourthly, other image parameters including the vertical pons hyperintensity which has been reported to be more sensitive than “hot cross bun” sign and “swallow-tail” sign were not evaluated ( 16 , 20 ). Finally, the absence of a definite postmortem diagnosis increases the likelihood of misdiagnosis in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Third, other image parameters including SWI scores of putaminal hypointensity ( 12 ), hyperintense putaminal rim, hyperintensity of the pons (“hot cross bun” sign, including only cruciform hyperintensity), brain stem atrophy, and cerebellar atrophy were also evaluated by the two readers ( 16 , 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…Postvoid residual urine volume was measured three times or more in each subject by ultrasonography, and the mean value was calculated. The head-up tilt test was performed for assessment of orthostatic hypotension as described previously [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…MCP hyperintensities were marked as present or absent, where present was defined as "when high intensities relative to that of the brainstem and cerebellum in the adjacent white matter were observed on at least one side of the MCP" (Fig 2). The HCB sign was graded as described in a previous study [26], where 0 denoted no changes; 1 indicated initial appearance or presence of a clear vertical T2 highintensity; and 2 indicated initial appearance of a horizontal line along with a vertical line or the presence of clear horizontal and vertical lines in the ventral pons (Fig 2). Here both grade 1 and grade 2 were defined as positive for HCB sign.…”
Section: Visual Interpretation Of Mcp Hyperintensities and The Hcb Signmentioning
confidence: 99%
“…The MCP volume was measured in all subjects by exploiting a validated probabilistic 3D atlas of the cerebellar white matter structure [26]. Parcellation at a 90% probability threshold was used.…”
Section: Mcp Volume Analysismentioning
confidence: 99%